1998
DOI: 10.1074/jbc.273.21.13339
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Binding Site for Transforming Growth Factor-β in Human α2-Macroglobulin to a 20-kDa Peptide That Also Contains the Bait Region

Abstract: and TGF-␤2 in fetal bovine heart endothelial (FBHE) cell proliferation assays; FP4 was inactive in this assay. FP3 also increased NO synthesis by RAW 264.7 cells, mimicking an ␣ 2 M activity that has been attributed to the neutralization of endogenously synthesized TGF-␤. Thus, we have isolated a peptide corresponding to 13% of the ␣ 2 M sequence that binds TGF-␤ and neutralizes the activity of TGF-␤ in two separate biological assays.1 is a 718-kDa glycoprotein that was originally characterized as a broad spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 67 publications
4
60
0
Order By: Relevance
“…In certain cases, such as TGF-β1 and PDGF, both the biochemical interaction of these molecules with α 2 M and the ability of α 2 M to regulate their function have been extensively studied (12,14,16,17,43,44). With regards to VEGF, an earlier study demonstrated that radiolabeled VEGF added to human plasma coprecipitates with α 2 M (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain cases, such as TGF-β1 and PDGF, both the biochemical interaction of these molecules with α 2 M and the ability of α 2 M to regulate their function have been extensively studied (12,14,16,17,43,44). With regards to VEGF, an earlier study demonstrated that radiolabeled VEGF added to human plasma coprecipitates with α 2 M (22).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cytokines and growth factors are known to bind to α 2 M and α 2 M-MA, including transforming growth factor beta (TGF-β), types 1 (11,12) and 2 (13,14), platelet derived growth factor (PDGF) (15)(16)(17), nerve growth factor (NGF) (17,18), tumor necrosis factor alpha (TNF-α) (19), basic fibroblast growth factor (bFGF) (20), interleukin six (IL-6) (21), and vascular endothelial growth factor (VEGF) (22). In some cases, such as TGF-β1, the nature of the interaction is well investigated whereas in others, such as VEGF, the nature of the interaction is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The hemopexin domain of MMP9, which includes the LRP1-binding site in MMP9 (MMP9-PEX; Mantuano et al, 2008a,b), was expressed as a GST fusion protein in bacteria. MMP9-PEX was partially purified by selective detergent extraction (Webb et al, 1998) and then purified to homogeneity by chromatography on a glutathione-Sepharose column (Mantuano et al, 2008a,b). All GST fusion proteins were subjected to urea treatment, dialysis and chromatography on Detoxi-Gel endotoxin-removing columns (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…␣ 2 M-peptide-GST Fusion Proteins-Six previously described fusion proteins, which collectively encode amino acids 99 -1451 of the human ␣ 2 M sequence, were expressed in BL-21 cells (17,18). These fusion proteins include: FP1 (aa 99 -392), FP2 (aa 341-590), FP3 (aa 591-774), FP4 (aa 775-1059), FP5 (aa 1030 -1279), and FP6 (aa 1242-1451).…”
Section: Methodsmentioning
confidence: 99%
“…The first involves a region within intron 17, at the 5Ј splice acceptor site for exon 18 (14). This exon is important because it encodes part of the bait region, where proteinases initiate reaction with ␣ 2 M by cleaving susceptible peptide bonds (15,16), and a segment of the growth factor binding sequence (17)(18)(19). In the second A2M gene polymorphism, Val-1000 is replaced by Ile (20).…”
mentioning
confidence: 99%